Racial Inequities in Asthma Care - Okelo, Sande O. (Seminars in Respiratory and Critical Care Medicine, 2022)
Racial inequities in asthma care are evolving as a recognized factor in long-standing inequities in asthma outcomes (e.g., hospitalization and mortality). Little research has been conducted regarding the presence or absence of racial inequities among patients seen in asthma specialist settings, this is an important area of future research given that asthma specialist care is recommended for patients experiencing the poor asthma outcomes disproportionately experienced by Black and Hispanic patients. This study provides a systematic review of racial asthma care inequities in asthma epidemiology, clinical assessment, medication prescription, and asthma specialist referral practices.
Keywords: asthma; race/ethnicity; racial inequities; care quality; specialist care; strategies